"Becoming" a mentor between reflective and evaluative discourses: A case study of identity development. (November 2020) - Lammert, Catherine; DeWalt, Lora M.; Wetzel, Melissa Mosley
Abstract: This case study interpreted the experiences of a teacher as she grew her coaching and mentoring practices by working with preservice teachers and participating in professional development focused on reflective coaching, mentorship, and literacy teaching. We drew on the notion of "becoming" from critical and sociocultural theories in analyzing how she constructed a teaching identity through mentoring, and how her identity enabled her to enact reflective coaching practices. Our findings outline her agentic moves to provide the preservice teacher with reflective support, rather than evaluative critique, in opposition to the surveillance and regulation that characterize many existing teacher evaluation models. Highlights: Teachers' identities are continuously constructed through negotiation of different discourses. Reflective coaching allows mentors to support, rather than simply evaluate, preservice teachers. Professional development in reflective coaching supports teachers' agentic stance-taking. Teachers can adopt reflective models of mentorship even when evaluative models are prominent.